Unmet need for family planning and associated factors among adolescent girls and young women in Ethiopia: a multilevel analysis of Ethiopian Demographic and Health Survey - Desale Bihonegn Asmamaw; Wubshet Debebe Negash (BMC, 2023)
Abstract Background Unmet need for family planning among adolescent girls and young women (AGYW) is a common cause of the low contraceptive utilization in developing countries, including Ethiopia. To address problems associated with unmet for family planning among adolescent girls and young women nationally available evidences are essential. However, there is limited evidence regarding factors associated with the unmet need for family planning among adolescent girls and young women in Ethiopia. Hence, this study aims to assess the prevalence and associated factors of unmet need for family planning among adolescent girls and young women in Ethiopia. Methods Our analysis was based on secondary data using the 2016 Ethiopian Demographic and Health Survey data. A total weighted sample of 1086 adolescent girls and young women was included in this study. A multi-level mixed-effect logistic regression analysis was fitted. Adjusted odds ratios with 95% confidence intervals were used to show the strength and direction of the association. Statistical significance was declared at a p-value less than 0.05. Results The prevalence of unmet need for family planning was 28.3% (95% CI: 25.7, 31.0). Adolescent girls and young women age 15-19 years (aOR: 2.4, 95%CI: 1.3, 4.3), household wealth quantile; poor (aOR: 5.6, 95%CI: 2.8, 11.1) and middle (aOR: 2.9, 95%CI: 1.4, 6.0), had no media exposure (aOR: 2.1, 95%CI: 1.1, 4.1), and adolescent girls and young women from developing regions (aOR: 5.1, 95%CI: 1.1, 14.5) were significantly associated with unmet need for family planning. Conclusions Unmet need for family planning was high among adolescent girls and young women when compared to the national average and the United Nations sphere standard of unmet need for family planning. Age, wealth quantile, media exposure, and region were significantly associated with unmet need for family planning. Hence, there is the need to implement consistently effective family planning policies among AGYW living in developing regions of Ethiopia. Moreover, Public health policies and interventions that improve the existing strategies to improve media exposure of AGYW on family planning issues and increase the wealth status of households should be designed and implemented to reduce the unmet need for family planning in Ethiopia.